Pelatihan Teknologi Informasi dan Komunikasi dalam Project Based Learning Matakuliah Bahasa Inggris Mahasiswa Program Studi Kesehatan Masyarakat STIK Bina Husada Palembang - Agus Wahyudi; Arief Pamuji; Ririn Martuti (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service activity aims to introduce Information and Communication Technology (ICT) and apply it to Project-Based Learning (PjBL) in English courses for students of the Public Health Study Program at STIK Bina Husada Palembang. The focus of this training is on the use of ICT in this case the Canva and Google Translate applications. The methods used include lectures, discussions and practices, with the ultimate goal that students can produce technology-based projects in the form of educational posters in English. The results of the study showed a significant increase in ICT skills, self-confidence, and the ability to communicate using English. Students also showed good collaboration in groups, and were better prepared to face the challenges of the world of work that increasingly utilizes technology and cross-cultural communication, especially in the public health sector. This Community Service activity concluded that the integration of ICT and English in project-based learning can strengthen student competencies and prepare them to contribute effectively to the completion of students' English projects.